2018
DOI: 10.1111/imm.12982
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing a pH‐switch anti‐C5 antibody as a tool for human and mouse complement C5 purification and cross‐species inhibition of classical and reactive lysis

Abstract: SummaryC5 plays a major role in complement activation; C5 convertase cleaves C5 into the pro‐inflammatory C5a, and C5b, the nidus for the formation of the lytic membrane attack complex. C5 is a major target for anti‐complement drugs, necessitating better methods for the study of C5 function. Purification of C5 is complicated; classical methods involve precipitation or pH shifts that result in functional loss and low yield. We here present a method for C5 purification using a novel anti‐C5 monoclonal antibody (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Three of these human C5‐blocking mAb were selected for further characterization; testing for inhibition in other species showed that two of the mAb, 7D4 and 4G2 (both against C5 α chain), inhibited C5 in rat, rabbit, guinea pig and mouse sera, whereas 10B6 (against C5 β chain) was human‐specific. RO7112689 bound the C5 β chain, as reported previously, and was a weak inhibitor of guinea pig and mouse C5 (Fig. ), whereas Eculizumab bound C5 α and is human‐specific .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Three of these human C5‐blocking mAb were selected for further characterization; testing for inhibition in other species showed that two of the mAb, 7D4 and 4G2 (both against C5 α chain), inhibited C5 in rat, rabbit, guinea pig and mouse sera, whereas 10B6 (against C5 β chain) was human‐specific. RO7112689 bound the C5 β chain, as reported previously, and was a weak inhibitor of guinea pig and mouse C5 (Fig. ), whereas Eculizumab bound C5 α and is human‐specific .…”
Section: Discussionsupporting
confidence: 80%
“…CP haemolytic activity in serum was essentially absent at 2 hr post‐induction in 4G2‐treated animals but at later time‐points, residual haemolytic activity of approximately 35% of controls was detected (Fig. c), probably due to the high sensitivity of the haemolytic assay for residual C5 . As expected, serum from the untreated control animals retained full haemolytic activity across the time course.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Crovalimab binds to the C5 b-chain and prevents cleavage of the wild-type and SNP C5 by the C5 convertase. In addition, crovalimab uniquely inhibits C5b6 deposition on membranes, 8,9 further limiting membrane attack complex-mediated tissue damage. SMART has led to limited C5 accumulation and increased C5 binding capacity in nonhuman primates.…”
Section: Introductionmentioning
confidence: 99%